KAJIAN LITERATUR SISTEMATIS TENTANG UPAYA MENINGKATKAN KOMPETENSI COMPUTATIONAL THINKING CALON GURU - Syaflita, Dina; Riksa Yustiana, Yusi; Kaniawati, Ida (STKIP Pesisir Selatan, 2023)
Computational thinking (CT) has gained attention in various levels of education, particularly in higher education. The importance of CT competency in problem-solving has led to the conclusion that CT needs to be developed through the learning process. Therefore, prospective teachers become the main target for enhancing CT competencies. The aim of this research is to conduct a systematic literature review on efforts to improve CT skills in pre-service teachers. The research method used is a comprehensive search of various databases, specifically Scopus, using the keywords